Peran Festival Wisata Kuliner Sebagai Bentuk Pengembangan Destinasi Wisata Desa Kedungpari - Agung Satria Bimantara; Dhian Satria Yudha Kartika; Farhan Kusuma Waradana; Fikriyatun Nabila; Hikmah Saptya Ningrum; Muhammad Alief Hidayatulloh; Shahna Naila Safira (BADAN PENERBIT STIEPARI PRESS, 2023)
This study discusses the role of culinary tourism festivals in developing village tourist destinations, with a focus on Kedungpari village. The main objective of this study is to identify the contribution of culinary tourism festivals in increasing village tourism, strengthening the local economy, and promoting culture and culinary traditions in Kedungpari village. The method used in this study is direct observation by providing information directly as well as (online) and indirectly (offline) via posters. This study uses a qualitative method with a descriptive research type to explain how the Culinary Tourism Festival is held into three stages, namely preparation, implementation, and activity reporting. The results of the study show that culinary tourism festivals have a significant role in the development of tourist destinations in Kedungpari Village. This festival contributes to the promotion of village tourist destinations, increasing tourist visits, empowering the local economy, and preserving cultural and culinary traditions. This research can be a basis for policy makers and related parties in strengthening and developing culinary tourism festivals as a strategy for developing sustainable village tourism destinations